Hydrogen bonding to hexafluoroisopropanol controls the oxidative strength of hypervalent iodine reagents - Colomer, I; Batchelor-McAuley, C; Odell, B; Donohoe, T; Compton, R (American Chemical Society, 2016)
Hexafluoroisopropan-2-ol (HFIP) has been found to be an unusually beneficial solvent for undertaking hypervalent iodine-initiated [2+2] cycloaddition of styrenes. For the initiator phenyliodine(III) diacetate (PIDA), voltammetric data demonstrate that the enhanced reactivity in HFIP is due to its greater oxidizing abilities in this fluorinated solvent such that in HFIP the reactivity of PIDA is comparable if not superior to its fluorinated analog phenyliodine(III) bis(trifluoroacetate). These results contrast with the often reported view that the role of the fluoroalcohol is to stabilize a radical cation formed by single electron transfer. Moreover, combined NMR and HRMS results reveal the formation of a strong H-bonded adduct between the solvent and oxidizing reagent which is the physical origin of the observed altered synthetic reactivity.